2008
DOI: 10.1002/eji.200737687
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and interleukin 5 production by CD8hiCD57+ T cells

Abstract: CD8hi CD57 + T cells have previously been described as effector memory T cells with minimal expansion capacity and high susceptibility to activation-induced cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 26 publications
6
50
0
Order By: Relevance
“…The increase in frequency could result from preferential survival/maintenance of this population as opposed to CD8 + CD57 2 T cells, upregulation of CD57 on CD57 2 cells, something that normally occurs upon persistent antigenic stimulation (45), or through division of pre-existing CD57 + cells. Although CD57 has been associated with replicative senescence (46), these cells are able to divide under conditions where costimulatory factors are present (34). Regardless, high frequencies of CD8 + CD57 + cells were present in EBV-infected cultures from CMV + children, and their proportions correlated strongly to secreted IFN-g levels and thus to restriction of B cell expansion and memory formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in frequency could result from preferential survival/maintenance of this population as opposed to CD8 + CD57 2 T cells, upregulation of CD57 on CD57 2 cells, something that normally occurs upon persistent antigenic stimulation (45), or through division of pre-existing CD57 + cells. Although CD57 has been associated with replicative senescence (46), these cells are able to divide under conditions where costimulatory factors are present (34). Regardless, high frequencies of CD8 + CD57 + cells were present in EBV-infected cultures from CMV + children, and their proportions correlated strongly to secreted IFN-g levels and thus to restriction of B cell expansion and memory formation.…”
Section: Discussionmentioning
confidence: 99%
“…CD8 + CD57 + T cells are known to be potent IFN-g producers (25,34) and thus their high frequencies in EBV-infected cultures may contribute to the high IFN-g levels seen therein. We tried to assess IFN-g production in CD8 + CD57 + versus CD8 + CD57 2 T cells in response to the in vitro infection.…”
Section: High Frequencies Of Cd8 + Cd57 + T Cells In CMV + 2-y-old Chmentioning
confidence: 99%
“…Although CD57 is generally regarded as a marker of senescence in CD8 ϩ T cells, 13,19,20 a recent study showed that CD57 ϩ CD8 hi T cells are capable of proliferation in response to other stimuli. 21 Thus, CD57 ϩ T cells may not be "end-stage" effector T cells incapable of proliferation but may represent a highly differentiated subset of T cells capable of rapid cell division, cytotoxicity, and IFN-␥ production, as well as secretion of IL-5. 21 A total of 30% to 60% of CD56 dim CD16 bright NK cells in healthy adults express CD57, which is not expressed on immature CD56 bright NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…21 Thus, CD57 ϩ T cells may not be "end-stage" effector T cells incapable of proliferation but may represent a highly differentiated subset of T cells capable of rapid cell division, cytotoxicity, and IFN-␥ production, as well as secretion of IL-5. 21 A total of 30% to 60% of CD56 dim CD16 bright NK cells in healthy adults express CD57, which is not expressed on immature CD56 bright NK cells. 7,22 Fetal and newborn NK cells do not express or express low amounts of CD57, 23 and CD57 expression on NK cells increases with age.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that CD8 + CD57 + T cells are highly differentiated antigen‐driven effector cells in a state of replicative senescence with limited capacities to proliferate 88, 89, 90, 91, 92. Recent reports, however, suggest that these CD8 + CD57 + CD28 − T cells might comprise a rather heterogeneous group of highly antigen‐experienced cells that, depending on the immunobiological context and stimuli, differ in their susceptibility to apoptosis and their capability to proliferate and expand 84, 93, 94, 95…”
Section: Pathomechanisms In Ibmmentioning
confidence: 99%